Thermal and nonthermal pretreatment methods for the extraction of anthocyanins: a review - Ijod, Giroon; Musa, Farah Nurhusna; Anwar, Farooq; Suleiman, Norhidayah; Mohd Adzahan, Noranizan; Mohamad Azman, Ezzat (Wiley, 2022)
Functional plant bioactive such as polyphenols have drawn greater interest for researchers, food industries, and consumers. Anthocyanins are popular due to its high antioxidant activity and nutra-pharmaceutical potential. As the demand for anthocyanins grows, exploring and acknowledging applications of various conventional and nonconventional means of anthocyanin extraction is important. Conventional extraction methods have some limitations in the context that these are most time-consuming, tedious, and less cost-effective as well as offer lower extraction yield and selectivity. Therefore, to encounter the limitations mentioned, pretreatments including thermal and nonthermal are applied to plant materials prior to the conventional bioactive extraction process. Thermal pretreatments include blanching, ultrasonication, microwave, and ohmic heating (OH); meanwhile, examples of nonthermal pretreatment are enzymatic, high-pressure processing (HPP), and pulsed electric field (PEF). This review is an attempt to critically summarize the applications of various pretreatment methods for improving the extraction rates and yields of anthocyanins from plant materials.